PRODUKSI PROGRAM VARIETY SHOW “NGOPI” SEBAGAI MEDIA HIBURAN DAN EDUKASI DI TVRI BALI - Pande Putu Argyananta Artana; Ida Bagus Hari Kayana; Made Rai Budaya Bumiarta (UPT Pusat Penerbitan LP2MPP ISI Denpasar, 2026)
The NGOPI (Ngobrolin Orang Penuh Inspirasi) variety show is designed as an entertainment and educational program produced and broadcast via live streaming on the YouTube channel